Thesis supervision as a dialogic relationship: the importance of feedback in writing teaching practices (Praxis Educativa, 2025)
The increase in enrollment in doctoral programs worldwide has highlighted the importance of the supervisor-thesiscandidate relationship. Within this context, the article explores feedback practices from a dialogic perspective,aiming to move beyond one-way communication to create a space for exchange where doctoral students can developtheir critical thinking. The analysis of fifty-nine surveys conducted with doctoral students in the Social Sciences andHumanities indicated that dialogic feedback practices are particularly prominent in the socio-affective dimension ofthe supervisor-student relationship, while the cognitive aspects of feedback tend to be limited to corrections andsuggestions related to written work. Besides, participation in academic socialization instances fosters a dialogicrelationship between students and supervisors by sharing work dynamics and practices characteristic of the academicfield.
Keywords: thesis supervision; dialogic pedagogical practices; feedback; doctoral writing